Maternal Knowledge of Stunting in Toddlers: A Cross-Sectional Study in Indonesia - Rosmiati, Rosmiati; Wulansari, Eka; Marhumi, Marhumi (Chakra Brahmanda Lentera Institute, 2025)
Background: Stunting remains a major public health issue in Indonesia, where maternal knowledge is a critical factor for prevention. However, limited evidence exists regarding the specific knowledge gaps of mothers in semi-urban communities in Indonesia, which hampers targeted interventions. This study aimed to analyze maternal knowledge levels regarding stunting and its associated factors. Methods: This research utilized a descriptive cross-sectional design (reported according to STROBE guidelines) with 265 mothers of toddlers selected via stratified random sampling. Sample size justification and detailed inclusion/exclusion criteria were included. A validated and reliable questionnaire (Cronbach's α=0.87) was used. Data were analyzed using the Chi-Square test. Results: Most respondents (71.7%) had a good knowledge level. However, a statistically significant knowledge deficit was found concerning the specific causes of stunting (χ2=49.900;p<0.001). Factors such as education and employment status were significantly associated with knowledge levels. Conclusion: While general awareness of stunting is high, a critical gap exists in mothers' understanding of its complex causes. Educational interventions must become more focused. Future studies should employ longitudinal or interventional designs to assess the causal pathways between maternal knowledge and stunting prevention behaviors (Harmonized with Practical Implications).